Trojański palimpsest. Odniesienia intertekstualne w zakończeniu III księgi „Dziejów” Tacyta - Pigoń, Jakub (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The Trojan War or, more precisely, the sacking of Troy, plays an important role in the Roman cultural imagination and the crucial text dealing with these events, Vergil’s Aeneid II, has been used by various authors in various literary genres in order to build associations between their own subject matter and the fates of Priam, Hecuba, Aeneas etc. Thus, for example, the death of Agamemnon in Seneca’s tragedy of the same title bears a similarity to the death of Priam in the Aeneid; the two narratives are examined in the first part of the paper. In the main part of the paper, we move from Seneca to Tacitus; here, after a brief consideration of a passage from the account of the death of Galba (Hist. I 41, 3), there is a detailed discussion of one chapter from the end of Book III of the Histories (84). The chapter describes the Vitellian soldiers’ last stand against the Flavian army in Rome on December 20, AD 69 and Emperor Vitellius’ pathetic demise. The paper’s particular focus is on intertextual references which, so it seems, are introduced by Tacitus into his narrative to make his account of the last stage of the Roman Civil War of AD 68/69 more graphic and memorable; importantly, most of these references evoke the Trojan War and its aftermath. In particular, the following passages are analysed: (1) Tac. Hist. III 84, 2 ~ Verg. Aen. II 501–502; (2) Tac. Hist. III 84, 3 ~ Sall. Cat. 52, 3 + Eur. Hec. 568–570 (cf. Ov. Met. XIII 879–880; Fast. II 833–834); (3) Tac. Hist. III 84, 4 ~ Verg. Aen. II 755; (4) Tac. Hist. III 84, 5 ~ Verg. Aen. II 57–59.